2021
DOI: 10.1080/19942060.2021.1918259
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis on heat-flow-coupled temperature field for orthogonal face gears with oil–jet lubrication

Abstract: Lubrication and cooling performances of face gears with oil-jet lubrication are closely related to the nozzle layouts. To investigate the influence of the nozzle layouts on the lubrication performance of the face gears, a numerical analysis method based on heat-flow coupling is adopted in this study for predicting the transient temperature characteristics. First, a mathematical model of impingement depth integrating the nozzle spatial layouts, injection parameters, and geometric parameters of the given face ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Ouyang et al [25] investigated the jet lubrication of orthogonal face gear pair and found that a reasonable nozzle layout can improve the lubrication reliability. Hu et al [14,15] proposed a model to estimate the oil churning power loss in a helicopter spiral bevel gear transmission gearbox and analyzed how different factors affect the lubrication reliability due to oil churning.…”
Section: Introductionmentioning
confidence: 99%
“…Ouyang et al [25] investigated the jet lubrication of orthogonal face gear pair and found that a reasonable nozzle layout can improve the lubrication reliability. Hu et al [14,15] proposed a model to estimate the oil churning power loss in a helicopter spiral bevel gear transmission gearbox and analyzed how different factors affect the lubrication reliability due to oil churning.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers [5,6] have come up with similar results validating through experiments that the nozzle location affects the oil-air ratio and total pressure. On this basis, the complex impingement depth model is extended for the face gear and spiral bevel gear [32][33][34]. However, the aforementioned literature determined the nozzle layouts judged by the oil-air ratio and total pressure which are hard to measure directly through an indirect method.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Massini et al 6 carried out experiments on a novel rotating test bench capable of reproducing real aero-engine working conditions for single spur gear, experimental findings showed that under high Reynold number oil jet breakup happens, is detrimental for the lubrication and cooling of the target gears due to part of the oil escaping and not reaching the gear, on the other hand, the impingement velocity of oil jet reduced. By analyzing the oil jet lubrication process and meshing theory of helical/face gear pair, Dai et al 7,8 and Ouyang et al 9 further developed novel mathematical models of impingement depth closely associated with nozzle arrangement, the relationship between the measured temperature by experiments and the corresponding theoretical impingement depth indicates that a lower temperature comes with a larger impingement depth. So far, experimental researches on the detail of the flow field from the nozzle to the target parts are relatively weak.…”
Section: Introductionmentioning
confidence: 99%